Protective effect of phytoestrogens on nonalcoholic fatty liver disease in postmenopausal women - Zhao, ChenLu; Shi, JunHao; Shang, DongFang; Guo, Min; Zhou, Cheng; Zhao, WenXia (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a progressive metabolic disease characterized by hepatic steatosis, inflammation and fibrosis, which seriously endangers global public health. Epidemiological studies have shown that the incidence of non-alcoholic fatty liver disease in postmenopausal women is significantly increased. Studies have shown that estrogen deficiency is the main reason for this situation, and supplementing estrogen has become a new direction for preventing the occurrence of postmenopausal fatty liver.However, although the classical estrogen replacement therapy can reduce the incidence of postmenopausal NAFLD, it has the risk of increasing stroke and cardiovascular diseases, so it is not suitable for the treatment of postmenopausal NAFLD. More and more recent studies have provided evidence that phytoestrogens are a promising method for the treatment of postmenopausal NAFLD. However, the mechanism of phytoestrogens in preventing and treating postmenopausal NAFLD is still unclear. This paper summarizes the clinical and basic research evidence of phytoestrogens, and reviews the potential therapeutic effects of phytoestrogens in postmenopausal NAFLD from six aspects : improving lipid metabolism in liver and adipose tissue, improving glucose metabolism, reducing oxidative stress, reducing inflammatory response, blocking liver fibrosis, and regulating intestinal flora.